Navigating the transition of care in patients with inborn errors of immunity: a single-center’s descriptive experience - Mejía González, María Alejandra; Quijada Morales, Patricia; Escobar, María Ángeles; Juárez Guerrero, Alba; Seoane-Reula, María Elena (Frontiers in Immunology, 2023)
The transition from pediatric to adult care is a critical milestone in managing children, especially in those with complex chronic conditions. It involves ensuring the patient and family adapt correctly to the new phase, maintaining continuity of ongoing treatments, and establishing an appropriate follow-up plan with specialists. Patients with Inborn error of immunity (IEI), formerly known as Primary Immune Disorders (PID) are part of a group of disorders characterized by alterations in the proper functioning of the immune system; as the diagnostic and treatment tools for these entities progress, life expectancy increases, and new needs emerge. These children have special needs during the transition. Particularly important in the group of children with PID and syndromic features, who often present multiple chronic medical conditions. In these cases, transition planning is a significant challenge, involving not only the patients and their families but also a wide range of specialists. To achieve this, a multidisciplinary transition team should be established between the pediatric specialists and the adult consultants, designing a circuit in which communication is essential. As few transition care guidelines in the field of PID are available, and to our knowledge, there is no specific information available regarding patients with PID associated with syndromic features, we share our experience in this issue as a Primary Immunodeficiencies Unit that is a National Reference Center for PID, and propose a guide to achieve an adequate and successful transition to adulthood in these patients, especially in those with associated syndromic features.